2013
DOI: 10.1007/s13404-013-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer processes on Au nanoclusters supported on graphite

Abstract: Electron transfer processes play an important role in surface chemistry. This paper presents results of a study of changes in resonant electron transfer processes, as a function of gold cluster sizes, on the example of electron transfer between Li + ions scattered on Au clusters on highly oriented pyrolytic graphite (HOPG). The gold nanoclusters were grown on lightly sputtered HOPG surface in order to obtain a wide coverage distribution of clusters. The growth of clusters was monitored by scanning tunneling mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Such a behavior has been observed in low energy alkali ion scattering from Au and Ag nanoclusters in Refs. [48,50,51], and a decrease of edge atom charge for clusters that are smaller than those considered here may be the reason. Thus, the extrapolation of the model to a cluster diameter of zero in Figs.…”
Section: Modelmentioning
confidence: 77%
See 2 more Smart Citations
“…Such a behavior has been observed in low energy alkali ion scattering from Au and Ag nanoclusters in Refs. [48,50,51], and a decrease of edge atom charge for clusters that are smaller than those considered here may be the reason. Thus, the extrapolation of the model to a cluster diameter of zero in Figs.…”
Section: Modelmentioning
confidence: 77%
“…This is because the alkali LEIS technique is adept for studying surfaces composed of multiple elements and can address questions about the charge state of those elements. Previous results have shown that the ions scattered from Au and Ag nanoclusters on an oxide and other substrates have a much higher neutralization probability than those scattered from the bulk metal, and that neutralization decreases as the cluster size increases [48][49][50][51][52][53][54][55]. Although it is possible that the alkali LEIS neutralization rate and the Au nanocluster catalytic activity are related, such a correlation has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Au nanoclusters were grown on sputtered highly ordered pyrolytic graphite (HOPG) 23 and Al 2 O 3 surfaces and on pristine HOPG. We find that significantly more efficient Li + neutralization occurs on small clusters grown on alumina and slightly bombarded HOPG, with neutralization decreasing as the cluster size increased.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bonding to such π orbitals could remove charge from the edge atoms in a similar manner as for Au bonding to a substrate O atom. The NF for low energy Li + scattered from Au nanoclusters supported on HOPG show a similar decrease of the NF as a function of Au coverage [66,67], which suggests that the bonding of the edge atoms to the substrate is via π orbitals for both single layer Gr and bulk graphite surfaces.…”
Section: Discussionmentioning
confidence: 84%